Engineering a Human Pluripotent Stem Cell-Based in vitro Microphysiological System for Studying the Metformin Response in Aortic Smooth Muscle Cells - Chen, Nan; Abudupataer, Mieradilijiang; Feng, Sisi; Zhu, Shichao; Ma, Wenrui; Li, Jun; Lai, Hao; Zhu, Kai; Wang, Chunsheng (Frontiers in Bioengineering and Biotechnology, 2021)
Aortic aneurysm is a common cardiovascular disease characterised by continuous dilation of the aorta, and this disease places a heavy burden on healthcare worldwide. Few drugs have been suggested to be effective in controlling the progression of aortic aneurysms. Preclinical drug responses from traditional cell culture and animals are usually controversial. An effective in vitro model is of great demand for successful drug screening. In this study, we induced an in vitro microphysiological system to test metformin, which is a potential drug for the treatment of aortic aneurysms. Human pluripotent stem cell-derived aortic smooth muscle cells (hPSC-HASMCs) were cultured on an in vitro microphysiological system, which could replicate the cyclic stretch of the human native aortic wall. By using this system, we found that HASMCs were more likely to present a physiologically contractile phenotype compared to static cell cultures. Moreover, we used hPSC-HASMCs in our microphysiological system to perform metformin drug screening. The results showed that hPSC-HASMCs presented a more contractile phenotype via NOTCH 1 signalling while being treated with metformin. This result indicated that metformin could be utilised to rescue hPSC-HASMCs from phenotype switching during aortic aneurysm progression. This study helps to elucidate potential drug targets for the treatment of aortic aneurysms.